Exploring the nature of visual fixations on other pedestrians. (June 2018) - Fotios, S; Uttley, J; Fox, S
How we look at other people may affect conclusions drawn about the effect of changes in lighting when this task needs to be done after dark. This paper reports further analysis of the distance and duration of fixation on other pedestrians, updating a previous review by considering a greater number of fixations and by examining the influence on these of other characteristics such as the relative direction of travel. This analysis provides further support for a tendency to fixate others at a distance of 15 m and for a duration of 500 ms.